Scoping review and thematic analysis of informed consent in humanitarian emergencies - Thomson, Benjamin; Mehta, S.; Robinson, C. (BMC medical ethics, 2024)
Background To identify and to summarize challenges related to the informed consent process for research completed during humanitarian emergencies. Methods Using relevant search terms, a search of 5 databases was completed, without language, date, or study type restriction. Studies were screened for inclusion, with eligible studies being those that were relevant to the informed consent process for research studies completed in humanitarian emergencies. A Grounded Theory Analysis was completed to identify themes and subthemes. Results Review identified 30 relevant studies. We identified 11 challenges (lack of trust, therapeutic misconception, reduced capacity, security and privacy concerns, harmful research, power differential, literacy, language/local and cultural context, researcher burden and re-evaluation of ongoing trials) and 7 strategies (engage local research communities, use alternative to standard written consent process, modify traditional process of research ethics board review, dynamic consent, training of research staff, mandating transparency of commercial interests, and mandating reporting of informed consent process in all publications) to confront the challenges. These challenges and strategies were unique to the informed consent process in research conducted during humanitarian emergencies. Conclusions This scoping review identified an evidence-based guide for researchers and research ethics boards to perform ethical informed consent procedures in humanitarian emergencies. Trial Registration This trial was not registered as scoping reviews can not be registered as per updated PROSPERO guidelines.